Building impact at scale: What is scalability and scaling preparedness? - Black, Naomi (International Food Policy Research Institute, 2024)
In September and October, a series of important workshops were held in three countries —Nigeria, Uganda, and Ethiopia—where sustainable and inclusive agri-food system interventions are being piloted as part of the Rethinking Food Markets (RFM) Initiative. The focus of these workshops was to evaluate whether the intervention bundles tested in various country contexts and for different commodities could be scaled, and to identify what actions stakeholders could take to create the right conditions for successful scaling.